2015
DOI: 10.1186/s12978-015-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child communication about sexual and reproductive health: evidence from the Brong Ahafo region, Ghana

Abstract: BackgroundYoung people aged 10–24 years represent one-third of the Ghanaian population. Many are sexually active and are at considerable risk of negative health outcomes due to inadequate sexual and reproductive health knowledge. Although growing international evidence suggests that parent–child sexual communication has positive influence on young people’s sexual behaviours, this subject has been poorly studied among Ghanaian families. This study explored the extent and patterns of parent–child sexual communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
79
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 42 publications
13
79
4
5
Order By: Relevance
“…The rarely discussed topics to female adolescents by both sexes of caretakers are condom and other contraceptive use while to male adolescents, abstinence is rarely discussed by female caretaker and safer sex by male adolescents. Similar topics reported in many studies as the focus of discussion and the least discussed topics between caretakers and adolescents [5, 23, 34, 36], however studies did not differentiate topics communicated by different sex of caretaker to different sex of adolescents. This is the only study which report in details different sex-choice of topic of discussion by gender of adolescents.…”
Section: Discussionmentioning
confidence: 75%
“…The rarely discussed topics to female adolescents by both sexes of caretakers are condom and other contraceptive use while to male adolescents, abstinence is rarely discussed by female caretaker and safer sex by male adolescents. Similar topics reported in many studies as the focus of discussion and the least discussed topics between caretakers and adolescents [5, 23, 34, 36], however studies did not differentiate topics communicated by different sex of caretaker to different sex of adolescents. This is the only study which report in details different sex-choice of topic of discussion by gender of adolescents.…”
Section: Discussionmentioning
confidence: 75%
“…Studies elsewhere in sub-Saharan Africa have found significant barriers to communication about sex (Bastien, Kajula, and Muhwezi 2011). Parents are reluctant to discuss more than the adverse consequences of sexual activity, and maternal communications about sex are frequently restrictive and moralistic in tone (Bastien, Kajula, and Muhwezi 2011;Macleod and Tracey 2010;Manu et al 2015). In some Western societies, a more open communication and pragmatic view of youth sexuality prevails (Weaver, Smith, and Kippax 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that although there are other sources of information on sexuality, parents continue to be the preferred source (Manu et al, 2015). Likewise, it was found that peers and the media are alternative sources of information about sexuality that adolescents, especially women, trust more and experience less prejudice from (Martino et al, 2009;Regmi et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…Women are more likely to talk about the topic with their parents, especially with their mothers, than men (Jones, 2010;Kapungu et al, 2010). Although previous studies have established that parent-child communication about sexuality is limited, abstinence, menstruation, and prevention of sexually transmitted diseases have been identified as the topics most often addressed by parents (Manu, Mba, Asare, Odoi-Agyarko, & Asante, 2015). When discussing abstinence, female sexual activity is represented as rational only when the relations are based on love and a stable partnership (Jones, 2010).…”
mentioning
confidence: 95%
See 1 more Smart Citation